2001
DOI: 10.1097/00008390-200110000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in invasive cutaneous malignant melanoma: a population-based study and review

Abstract: A population-based study from Sweden identified 711 patients with cutaneous malignant melanoma diagnosed in 1965, 1975, 1985 and 1989. Prognostic factors were evaluated and a review of the literature was performed. On univariate analysis, thick tumours (> 0.8 mm) (odds ratio [OR] 1.8, 95% confidence interval [CI] 1.6-2.1), increasing Clark level (OR 1.8, 95% CI 1.6-2.0), ulceration (OR 1.8, 95% CI 1.6-2.0), nodular melanoma (OR 1.5, 95% CI 1.3-1.6) and increasing age (continuous variable, P < 0.0001) were asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 41 publications
7
54
1
2
Order By: Relevance
“…This is in accordance with a previous report [7] but at variance with two other reports [5,6]. Interestingly, patients with CMM in Sweden [32] and other countries [33,34] display a significantly longer survival among females than males. Multifactorial analyses have shown that gender is an independent prognostic factor for CMM [32,34].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with a previous report [7] but at variance with two other reports [5,6]. Interestingly, patients with CMM in Sweden [32] and other countries [33,34] display a significantly longer survival among females than males. Multifactorial analyses have shown that gender is an independent prognostic factor for CMM [32,34].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, patients with CMM in Sweden [32] and other countries [33,34] display a significantly longer survival among females than males. Multifactorial analyses have shown that gender is an independent prognostic factor for CMM [32,34]. Melanoma cells often display oestrogen receptors but there is no obvious relationship between the amount of sex hormones and survival in individuals with CMM [35].…”
Section: Discussionmentioning
confidence: 99%
“…Pleiotrophin, a heparin-binding protein involved in motility and angiogenesis, is expressed in melanoma but not nevi; by univariate analysis, its expression level correlates with melanoma-related survival [ 212 ]. The major pathologic and clinical prognostic factors that have been evaluated in multivariate analyses that included >450 cases and >5-year mean follow-up [ 213 ] are summarized in Table 14.7 .…”
Section: Miscellanymentioning
confidence: 99%
“…The 5-year survival with negative nodes was 97.9 % in another study [ 223 ]. Thus, lymph node involvement is often a bellwether event in Updated from Måsbäck et al [ 213 ] + signifi cant effect on prognosis, NS no signifi cant effect, − not examined a Number (%) of studies with effect on prognosis. Potency of the prognostic factors by multivariate analysis, in declining order: tumor thickness > mitotic rate > ulceration > age > gender > site >> Clark's level the natural history of melanoma.…”
Section: Prognostic Factors For Stage III Melanomamentioning
confidence: 99%
“…It has a high metastatic potential [1], and its incidence and mortality among the Caucasian population has increased markedly during the past three decades [2]. Accurate and reliable methods for the detection and grading of lesions and their extension are essential to allow early diagnosis and to evaluate new therapies, the two keys to success in tackling this important medical problem.…”
Section: Introductionmentioning
confidence: 99%